Numerical simulation of hydraulic optimization for regulating tank in pumping station. Issue 1 (October 2021) - Zhu, Xiaoming; Shi, Sha; Si, Jing; Fitri, Arniza; Pratiwi, Dian; Agustina, Adelia
Abstract: Based on the governing equations of steady incompressible fluid, renormalization group (RNG) turbulence model and SIMPLEC algorithm are used to calculate the steady flow field of regulating tank in the pumping station with six different geometries operating under same condition. The impacts of the layout schemes of guide walls for the flow field of the regulating tank are analyzed. The numerical results are verified by physical model experiment and good agreement is found. The results show that: 1) serious flow separation of side wall will occur in the regulating tank when the interval of diversion wall is 10 L; 2) the flow velocity in the regulating tank will be too low when the diversion wall spacing is 16 L; 3) the improvement of the flow pattern of the regulating tank is not obvious; and the project cost is increased when the excavation depth of the regulating tank is increased by 1 m; 4) the bottom velocity reached the non-silting velocity and the head loss of the regulating tank reducing nearly 1.2 m by using arrangement form of wide 21 L and narrow 10L of the guide walls, which provides a certain guarantee for the safe operation of the pumping station. The regulation tank layout scheme proposed in the paper can be applied to engineering practice.